Electrosynthesis of Composites Consisting of FeOOH and Reduced Graphene Oxide in Graphite Electrodes - de Oliveira, João Pedro Jenson; Vilalva, Júlia B.; de Sá, Acelino Cardoso; Paim, Leonardo Lataro (Orbital: The Electronic Journal of Chemistry, 2020)
Carbon-based composite nanomaterials, such as graphene oxide, have demonstrated a great potential for applications in several areas. The present work sought to obtain, via electrosynthesis, a composite material based on graphene oxide and iron oxyhydroxide deposited onto graphite pencil surface. The electrodes modifications by electrosynthesis was performed using the cyclic voltammetry technique. The graphene oxide and the electrosynthesized FeOOH cuboids were characterized by SEM-FEG, EDX. The cyclic voltammetry was used to characterize the electrochemical behavior of the graphite pencil electrode (PEG). The composites electrodes of PEG modified with GO/FeOOH (PEG/GO/FeOOH) were formed in two stages. In the first stage, there was the formation of FeHCF in PEG/GO, and subsequently, there was the formation of PEG/GO/FeOOH in alkaline medium. DOI: http://dx.doi.org/10.17807/orbital.v12i3.1477